Implementasi Extrem Programming Pada Pengembangan Repositori Digital Dokumen Pendukung Akreditasi Berbasis Web - Sulistyowati; Erfan, Muhammad; Suparno (Jurnal Informasi dan Teknologi, 2023)
This research was conducted with the aim of producing an application that could facilitate the management of accreditation document data for both institutions and study programs in the form of a digital repository within STMIK Palangkaraya. With this application, it is hoped that the preparation of Laporan Evaluasi Diri (LED), Laporan Kinerja Perguruan Tinggi (LKPT) and Laporan Kinerja Program Studi (LKPS) can be written and read in a comprehensive manner with a direct link to the documents referred to in the report. In addition, this application is expected to speed up the process of searching for accreditation supporting documents when an assessment is carried out by an assessor. The type of research used is Research & Development (R&D) in collaboration with the Extreme Programming (XP) system development method. The stages of the research followed the development cycle of the web-based XP method. The final result of this research is the Digital Repository Dokumen Akreditasi (DIREKSI) application which can provide document links and display documents directly web-based. This application can be accessed online via the URL https://direksi.stmikplk.ac.id.